(untitled) (translation. a transdisciplinary journal, 2021)
In this paper, I respond to the presentations by Anthony Pym and Gayatri Spivak delivered at the Nida Research Seminar held at the College Board in New York Ciry on September 14, 201 2. Pym’s paper was tided ’On lnculcuration’ and discussed the concept from the view of Pope John Paul II, in which he referred to ’inculcuration’ as ’the incarnation of the Gospel in autonomous cultures’ and ’the introduction of these culcures into the life of the Church’ (1985, 1 1).